PTU-064 Inflammatory bowel disease and fatigue: the effect of physical activity and/or omega 3 supplementation. (22nd June 2015) - McNelly, A; Nathan, I; Monte, M; Grimble, G; Norton, C; Bredin, F; Czuber-Dochan, W; Berliner, S; Gay, M; Darvell, M; Terry, H; Forbes, A
Abstract : Introduction: Fatigue is frequently reported by patients with Inflammatory Bowel Disease (IBD), despite disease remission. However, no previous intervention trial has studied this symptom. We tested the effects on fatigue in IBD patients from (i) individual advice to increase physical activity (PA) and/or (ii) supplementation with omega-3 fatty acids. Method: Design:a randomised controlled 2 × 2 factorial study compared change-from-baseline scores in intervention and control groups. Primary outcome: change in FACIT-F (Functional Assessment of Chronic Illness Therapy – Fatigue) score; main secondary outcomes: change in fatigue survey scores including IBD-fatigue (IBD-F); PA by monitors (Actigraph, Pensacola, US); adverse effects. Eligibility: IBD remission; ≤2 portions oily fish/week; ≤ 60 min moderate-vigorous PA/week; no comorbidities causing fatigue; no depression. Interventions: exercise advice (15 min consultation) and fish oil supplement (2.97 g per day omega-3, "Take Omega 3"©, Edinburgh, UK); Controls: dietary consultation and placebo supplement. All patients received follow-up support (email, telephone). Results: Over 640 IBD outpatients were screened: 74 of those eligible consented to inclusion and randomisation, 60 commenced the intervention, and 52 completed the study according to protocol. At baseline the four groups did not differ significantly (gender, age, disease location or past IBD activity, level of PA, or FACIT-F score). The only effect on fatigue from the primary outcome – significant deterioration in FACIT-F score (95% CI:-8.6-(-0.7); p = 0.02) – was with omega-3 supplement. Fatigue was however significantly reduced in the exercise groups, measured by IBD-F score (95% CI:-3.8-(-0.2); p = 0.03). There were no significant interactions between effects of exercise and fish oil on fatigue, or consistent trends in fatigue or PA levels across the various measures between the four groups. Only 1 treatment-related adverse event was reported (in exercise group), suggesting that neither exercise nor fish oil were associated with likelihood of occurrence of an adverse effect, including gastrointestinal symptoms. Conclusion: The apparent worsening of fatigue with fish oil is unexplained. Exercise and fish oil, singly or in combination, were shown to be safe and generally well-tolerated in IBD patients. There was no evidence of adverse exercise-related effects on gut-related symptoms, and some evidence of improvement in fatigue. Hence, regular moderate-vigorous exercise may provide self-management options in IBD-related fatigue. Disclosure of interest: A. McNelly Grant/ Research Support from: Big Lottery Fund in collaboration with Crohn's and Colitis UK, I. Nathan Grant/ Research Support from: Big Lottery Fund in collaboration with Crohn's and Colitis UK, Speaker Bureau of: Dr Falk Pharma UK, M. Monte: None Declared, G. Grimble: None Declared, C. Norton Grant/ Research Support from: National Lottery in collaboration with Crohn's and Colitis UK, Speaker Bureau of: Ferring; Shire, F. Bredin: None Declared, W. Czuber-Dochan Grant/ Research Support from: Big Lottery Fund in collaboration with Crohn's and Colitis UK, Speaker Bureau of: Dr Falk Pharma UK; Ferring, S. Berliner Consultant for: Crohn's and Colitis UK, M. Gay Consultant for: Crohn's and Colitis UK, M. Darvell Employee of: Crohn's and Colitis UK, H. Terry Employee of: Crohn's and Colitis UK, A. Forbes Grant/ Research Support from: Big Lottery Fund in collaboration with Crohn's and Colitis UK, Speaker Bureau of: Dr Falk Pharma UK; Warner-Chilcott; NPS.